THE IDEAL LEADERSHIP MODEL FOR SCHOOL PRINCIPALS IN OPTIMIZING STUDENT DEVELOPMENT IN ELEMENTARY MADRASAHS - Fauzan; Muhamad Ramli; Muhammad Helmi (Program Studi PGMI STAI Al Falah Banjarbaru, 2025)
This study aims to formulate an ideal model of school principal leadership for optimizing student development at Madrasah Ibtidaiyah, with the research conducted at MI Unggulan Al Falah in Banjarbaru. The background of this study stems from the importance of the school principal’s role as the primary driving force in creating a learning environment capable of fostering students’ holistic development, encompassing cognitive, affective, and psychomotor aspects. The research approach used is qualitative, specifically a case study. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using thematic analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the ideal principal leadership model is an integration of transformational, instructional, and spiritual leadership. An effective principal is capable of building a school culture that is collaborative, religious, and oriented toward the optimal development of students’ potential. This leadership focuses not only on administrative aspects but also on the professional development of teachers and the strengthening of students’ character. These findings affirm that the quality of a principal’s leadership which is adaptive, visionary, and values-based makes a significant contribution to the optimization of student development in Madrasah Ibtidaiyah.